Supervisory stress tests - Beverly Hirtle; Andreas Lehnert (Federal Reserve Bank of New York, 2014)
This article describes the background, design choices and particular details of stress tests used as part of an overall supervisory regime; that is, their formal integration into the process of the ongoing prudential supervision of banks and other large financial institutions. We then describe how the U.S. CCAR/DFAST regime is designed and what that means for the macroprudential vs. microprudential nature of the U.S. exercises. We argue routine stress tests have the potential to substantially change the nature of the supervisory process. In addition, we argue that a great deal depends on the philosophy underpinning modeling decisions, which has not received as much attention as scenario design, disclosure or other stress test design choices.
Keywords: G21; G01; 330; stress tests; bank capital